A STUDY ON IMPROVEMENT MARKETING PERFORMANCE OF INDONESIAN ORNAMENTAL FISH EXPORTERS - Zwespana, Anastasya; Ong, Leonnard (Cerdika: Jurnal Ilmiah Indonesia, 2023)
Export performance is an indication of the companies’ success in the export. High export performance is important for companies in terms of ensuring sustainability in the long term. Indonesia expected to be a major player in the global economy especially for live ornamental fish export industry, so “how the marketing performance strategy in Indonesia for permanent success?” like this thought significantly raised. The objective on this research aims to examine the effect of market orientation, product innovation on competitive advantage and the effect of competitive advantage on company performance. Type of the data in this study is descriptive qualitative research. The data collection technique for this research was to conduct in-depth interviews, observations and data analysis as well as related documents. To collect quality and sufficient data, researchers will make observations and In-depth interviews for this study and will conduct interviews with 6 (Six) informants who have been selected who really understand the ornamental fish marketing in this business. Credibility or validity of the data used the triangulation procedure. The findings all participants agreed on this case study research. Overall, market orientation, product innovation, and competitive advantage are interconnected factors that can contribute to a company's market success and performance. By understanding customer needs, offering innovative products, and establishing a competitive edge, a company can position itself for success in the market.